Narratives as instrumental research and as attempts of fixing meaning. The uses and misuses of the concept of “narratives” - Miriam Cihodariu (Journal of Comparative Research in Anthropology and Sociology, 2012)
Narratives are the most important means of fixing the meaning of events and of the social and cultural construction of reality. This is the main assertion of this text, together with a detailed explanation of what is to be understood by narratives and narrative research. A particular topic of the paper is what is meant when the concept of narrative is used in the social sciences, for not everyone seems to be talking about the same thing. The misuses of the term borrowed from the common language often pervade scientific speech when dealing with the concept of narratives. Narrative research has gained a lot of ground in the humanities in the past two decades; this paper shows the directions and patterns of this development and how the new branch – enabled by poststructuralist thought – can be put into the older frame of anthropological research. The truth that every truth is socially constructed is taken as granted by the new approach to narratives and this problematic is left behind in order to focus on the how of the construction of meaning. As already stated above, it is my hypothesis that narratives (not to be confused with narrative research in this respect) are one of the most important means of constructing and fixing meaning. Working with narratives can be confusing in a number of ways detailed in the paper, but also clarifying in the respect that it explores more and assumes less than the more traditional approaches of social sciences.